Analysis of Financial Literacy Level (Study on Students of the Faculty of Economics and Business, Khairun University) - Hasan, Afrinda; Taslim, Fadli Ali; Amiro, Suratno; Bachmid, Faradisa (Journal of International Conference Proceedings, 2024)
Using the measurement characteristics suggested by Chen and Volve, this study attempts to assess and evaluate the degree of financial literacy among students at Khairun University's Faculty of Economics and Business. Descriptive quantitative research using a questionnaire survey method is the methodology employed. 139 respondents were selected for this study using a purposive selection strategy combined with a non-probability sampling technique. By dividing the number of actual scores by the number of ideal scores and multiplying the result by 100 percent, data analysis was done at the percentage level. According to the study's findings, 67.58% of students at Khairun University's Faculty of Economics and Business are financially literate. It is on a medium scale according to the Chen and Volve financial literacy measurement index. The results of the examination of financial literacy levels were then found to be influenced by respondent demographic characteristics, including gender, GPA, and parents' income.